Morphological analysis of spirulina algae filled polylactic acid biofilm / Nur Farisha Mohd Adlie - Mohd Adlie, Nur Farisha (2023)
There is a growing public demand for fast biodegradable plastic especially in packaging industries. The development of biodegradable plastic is one of many solutions to this problem. The used of petroleum-based plastic are kindly worried because of its effect on the environment such as giving risk to the marine ecosystem and pollution to the land, water and so on. The used of polylactic acid in this project are directly a better way since it is one of the biodegradable polymers with a high rate of degradation. Polylactic acid is applied as it is a compostable alternative to many products. However, the application of PLA is constrained by its slow rate of deterioration and fragility. Spirulina algae was used as a filler for this biofilm because it can lower the cost and increase the degradation rate. The making of biofilm in this project was done by using the solution casting method. The polylactic acid beads were stirred with dichloromethane (DCM) as one of the effective chemical solvents for the PLA and the addition of algae in the mixture and the casting process. The study of morphological analysis in this project was showed the miscibility of polylactic acid and spirulina algae as well as the proven of polylactic acid and spirulina appearance in the biofilm.